Participation of Residents in makinga Development Plan of Phitsanulok Municipality Mueang District Phitsanulok - Chamchoy, Wanwisa; Bodeerat, Chot (Journal of Humanities and Social Sciences, Rajapruk University, 2022)
The objectives of this research were 1) to study the level of public participation in the local development plan, 2) to compare the differences of personal factors with the participation of the people in developing local development plans, and 3) to study problems, Obstacles, and solutions to the public participation in the preparation of local development plans of Phitsanulok City Municipality, Muang District, Phitsanulok Province. The sample group used as representative of the population in Phitsanulok Municipality, Muang District, Phitsanulok Province is 400 people, using Taro Yamane's formula at a 95% confidence level. The researcher chose to use statistics for data analysis as follows: Descriptive statistics by distributing it in terms of frequency, percentage, mean and standard deviation. Inferential statistics used in the test analysis are t-test and One-Way ANOVA. The results of the study were as follows: 1) The respondents expressed their opinions. The level of public participation in the preparation of local development plans. The overall average was moderate. 2) Personal factors in terms of age, marital status, occupation, and monthly income had different effects on the participation of the people in the preparation of local development plans of Phitsanulok City Municipality, Mueang District, Phitsanulok Province with statistically significant at a level of 0.05. and 3) Problems, obstacles, and solutions for public participation in the formulation of the local development plan of Phitsanulok City Municipality are: problems in the community are partisan that cause lack of cooperation and unity among the group, and people lack confidence in Board Capabilities and community president, and the municipality should cooperate in examining the capacity of each community committee. The municipality should cooperate to check the capacity of each community committee before certifying the establishment of a community committee.